Unveiling the effect of social media marketing activities on logistics brand equity and reuse intention - Xiaofang Lin; Abdullah Al Mamun; Mohammad Masukujjaman; Qing Yang (Humanities & Social Sciences Communications)
Abstract Reserving existing customers is significantly more meaningful than acquiring new customers, particularly for logistics service providers. This long-standing view emphasizes the importance of customer retention for maintaining favorable relationships between logistics service providers and their clients. Drawing on the framework of the stimulus-organism-response model, this study proposes a model that integrates entertainment, interaction, trendiness, customization, and electronic word-of-mouth to examine how social media marketing activities and trust affect brand equity and reuse intentions for logistics services, both directly and indirectly. Empirical evidence was obtained from an online survey using WeChat and QQ, which administered a structured questionnaire to individuals with prior experience in logistics services at least once a week. We collected the data using a purposive sampling method from 932 participants, who represented the demographic of adult Chinese consumers. By applying partial least squares structural equation modeling, this study shows that interaction, trendiness, customization, electronic word-of-mouth, and trust positively affect the brand equity of logistics services, while the effect of entertainment on brand equity is not significant. In addition, the brand equity of logistics services positively affects the logistics service reuse intention. Furthermore, the result of the mediation analysis revealed that brand equity mediates the connection between interaction, trendiness, customization, electronic word-of-mouth, trust, and logistics service reuse intention. This study’s uniqueness lies in its thorough analysis of logistics service providers’ social media marketing efforts, trust, and their combined impact on brand equity and reuse intention. This study offers valuable perspectives on the significance of brand equity within the logistics sector, emphasizing the importance of prioritizing brand equity enhancement to improve performance and competitive edge.